1996
DOI: 10.1021/jm950828+
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibitors of Acyl-CoA:Cholesterol Acyltransferase. 2. Structure−Activity Relationships of NovelN-(2,2-Dimethyl-2,3-dihydrobenzofuran-7-yl)amides

Abstract: Novel N-(2,2-dimethyl-2,3-dihydrobenzofuran-7-yl)amide derivatives 1 were synthesized and tested for their ability to inhibit rabbit small intestinal ACAT (acyl-CoA:cholesterol acyltransferase) and lower serum total cholesterol in cholesterol-fed rats. Among the synthesized compounds, N-(2,2,4,6-tetramethyl-2,3-dihydrobenzofuran-7-yl)amide derivatives showed potent ACAT inhibitory activity. The synthesis and structure-activity relationships of these compounds are described. A methyl group at position 6 of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…In the course of investigating the metathesis of conjugated diynes and aldehydes, it was found that 2,3-dialkylidenetetrahydrofurans were formed in the reaction between 3,5-diynols and aldehydes (Scheme ). Although a flash vacuum pyrolysis of 3-acyloxymethyl-2-methylfuran, an olefination of 2-alkylidenebutyrolactone, and a cyclocondensation of 2-cinnamoyl ketene dithioacetals with oxalyl chloride have been known as preparations of 2,3-dialkylidenetetrahydrofurans that have a further functionalizable diene moiety and are expected to be converted into various biologically interesting polycyclic furans, these methods have limitations in reactants . Herein, we report the domino synthesis of 2,3-dialkylidenetetrahydrofurans via skeletal reorganization of the Prins-cyclized intermediates derived from 3,5-diynols and aldehydes.…”
supporting
confidence: 58%
“…In the course of investigating the metathesis of conjugated diynes and aldehydes, it was found that 2,3-dialkylidenetetrahydrofurans were formed in the reaction between 3,5-diynols and aldehydes (Scheme ). Although a flash vacuum pyrolysis of 3-acyloxymethyl-2-methylfuran, an olefination of 2-alkylidenebutyrolactone, and a cyclocondensation of 2-cinnamoyl ketene dithioacetals with oxalyl chloride have been known as preparations of 2,3-dialkylidenetetrahydrofurans that have a further functionalizable diene moiety and are expected to be converted into various biologically interesting polycyclic furans, these methods have limitations in reactants . Herein, we report the domino synthesis of 2,3-dialkylidenetetrahydrofurans via skeletal reorganization of the Prins-cyclized intermediates derived from 3,5-diynols and aldehydes.…”
supporting
confidence: 58%
“…The cholesterol that enters the enterocyte is transferred to endoplasmic reticulum, where it can be esterified by ACAT-2. The role of ACAT-2 in intestinal cholesterol absorption has been demonstrated in many in vitro and in vivo studies [Clark and Tercyak, 1984;Kataoka et al, 1996;Miyazaki et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol esterification involves the covalent attachment of fatty acids to 3-position hydroxyl group of cholesterol to form cholesteryl esters. Employing a number of specific ACAT-2 inhibitors, several studies have shown a reduction in intestinal cholesterol absorption [Clark and Tercyak, 1984;Kataoka et al, 1996;Miyazaki et al, 2005]. Furthermore, ACAT-2 knock out mice are resistant to dietinduced hypercholesterolemia due to defective cholesterol esterification by intestinal cells [Buhman et al, 2000].…”
mentioning
confidence: 99%
“…The cholesterol that enters the enterocyte is transferred to endoplasmic reticulum, where it can be esterified by ACAT‐2. The role of ACAT‐2 in intestinal cholesterol absorption has been demonstrated in many in vitro and in vivo studies [Clark and Tercyak, 1984; Kataoka et al, 1996; Miyazaki et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol esterification involves the covalent attachment of fatty acids to 3‐position hydroxyl group of cholesterol to form cholesteryl esters. Employing a number of specific ACAT‐2 inhibitors, several studies have shown a reduction in intestinal cholesterol absorption [Clark and Tercyak, 1984; Kataoka et al, 1996; Miyazaki et al, 2005]. Furthermore, ACAT‐2 knock out mice are resistant to diet‐induced hypercholesterolemia due to defective cholesterol esterification by intestinal cells [Buhman et al, 2000].…”
mentioning
confidence: 99%